Impact of the Seattle Sweetened Beverage Tax on substitution to alcoholic beverages - Powell, Lisa M.; Leider, Julien (PLOS ONE, 2022)
Introduction Taxes are increasingly used as a policy tool aimed at reducing consumption of sugar-sweetened beverages (SSBs), given their association with adverse health outcomes including type 2 diabetes, obesity and cardiovascular disease. However, a potential unintended consequence of such a policy could be that the tax induces substitution to alcoholic beverages. The purpose of this study is to examine the impact of the 0.0175 per ounce Seattle, Washington, Sweetened Beverage Tax (SBT) on volume sold of alcoholic beverages. Methods A difference-in-differences estimation approach was used drawing on universal product code-level food store scanner data on beer (N = 1059) and wine (N = 2655) products one-year pre-tax (February-November, 2017) and one and two-years post-tax (February-November, 2018 and 2019) with Portland, Oregon, as the comparison site. Results At two-years post-tax implementation, volume sold of beer in Seattle relative to Portland increased by 7% (ratio of incidence rate ratios [RIRR] = 1.07, 95% CI:1.00,1.15), whereas volume sold of wine decreased by 3% (RIRR = 0.97, 95% CI:0.95,1.00). Overall alcohol (both beer and wine) volume sold increased in Seattle compared to Portland by 4% (RIRR = 1.04, 95% CI:1.01,1.07) at one-year post-tax and by 5% (RIRR = 1.05, 95% CI:1.00,1.10) at two-years post-tax. The implied SSB cross-price elasticities of demand for beer and wine, respectively, were calculated to be 0.35 and -0.15. Conclusions There was evidence of substitution to beer following the implementation of the Seattle SSB tax. Continued monitoring of potential unintended outcomes related to the implementation of SSB taxes is needed in future tax evaluations.